PEMANFAATAN BAKTERI PELARUT FOSFAT PENGINDUKSI HORMON IAA (Indol Acetic Acid) UNTUK PENINGKATAN PERTUMBUHAN KEDELAI ( Glycine max) - Sudarmini, Desak Putu; Sudana, I Made; Sudiarta, I Putu; Suastika, Gede (Journal of Agricultural Science and Biotechnology, 2018)
Soybean is one of the agricultural commodities that are needed to fulfil food nutrients of Indonesian people. The low production of this commodity in Indonesia has not yet been able to meet the high demand for soybean that reaches 2.8 million tons per year, so that the Indonesian government still import soybeans at the amount of 2.26 million tons annually. The low production of soybeans in Indonesia is due to several factors, one of which is the expensive price of chemical fertilizers The use of rhizobacteria as bio-controlling agents can increase the availability of nutrients as well as crop production. Phosphate solubilizing bacteria are rhizobacteria that have the capacity to solubilize bound phosphate as well as trigger the growth hormone IAA that is the main hormone that controls various physiological processes in plants. The current study aimed to investigate whether isolates derived from rhizospheres of Leguminosae plants can induce IAA hormone and foster the vegetative growth of soybeans. The research results showed that five out of nine isolates of the phosphate solubilizing bacteria are able to induce IAA hormone and foster the vegetative growth of soybeans. Isolate treatment that showed the best impact toward soybean growth was identified molecularly through PCR. The result of RHC6 isolate identification shows a DNA ladder size of 1300bp which is suitable with the primer used. Based on the phylogenetic analysis conducted, nucleotide sequence of RHC6 isolate from Bali has a high similarity (97%) to and a low genetic distance (0.018) from Brevundimonas diminuta isolate from the US.